2022
DOI: 10.1186/s13007-022-00952-5
|View full text |Cite
|
Sign up to set email alerts
|

MGIDI: a powerful tool to analyze plant multivariate data

Abstract: Background Commonly, several traits are assessed in agronomic experiments to better understand the factors under study. However, it is also common to see that even when several traits are available, researchers opt to follow the easiest way by applying univariate analyses and post-hoc tests for mean comparison for each trait, which arouses the hypothesis that the benefits of a multi-trait framework analysis may have not been fully exploited in this area. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…This method performs selection using genotype and ideotype distances formulated by the breeder, which can be a solution to weighting coefficients for economic traits or multicollinearity issues in other selection methods (Olivoto and Nardino, 2021). Olivoto et al (2022) reported that this selection method has advantages in terms of easy genotype ranking, strengths and weaknesses view, and the option to weigh each trait in genotype ranking. Several previous studies have reported the utility of this method in selecting superior genotypes under abiotic stress and mega-environments (Maranna et al, 2021;Singamsetti et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This method performs selection using genotype and ideotype distances formulated by the breeder, which can be a solution to weighting coefficients for economic traits or multicollinearity issues in other selection methods (Olivoto and Nardino, 2021). Olivoto et al (2022) reported that this selection method has advantages in terms of easy genotype ranking, strengths and weaknesses view, and the option to weigh each trait in genotype ranking. Several previous studies have reported the utility of this method in selecting superior genotypes under abiotic stress and mega-environments (Maranna et al, 2021;Singamsetti et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…So, the multi-environment trials (METs) model the magnificent efforts in modern breeding programs for the valid and reliable selection of genotypes. The reliability of prediction (the expected value is close to the visible value) is crucial for an appropriate genotype recommendation and delimitation of mega-environments [12,15,35]. According to Gauch and Zobel [55], to increase the accuracy of prediction in METs, researchers must utilize statistical models that have high prediction abilities [35].…”
Section: Discussionmentioning
confidence: 99%
“…The agronomic trials' purpose was to examine the impact of factor level/s on plant characteristics to describe, understand, and analyze natural processes under study [13][14][15]. Toward the end of the trial, the scholars often have more columns (one for each trait), which need analysis to come up with and make inferences on the factor (rows) performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations